Vai trò của thực hành sư phạm thường xuyên với phát triển năng lực tổ chức hoạt động khám phá xã hội của sinh viên ngành Giáo dục mầm non - Phạm, Minh Mục; Trần, Thị Hòa (Tạp chí Giáo dục, 2026)
In the context of competency-based teacher education reform, continuous pedagogical practice is widely recognized as a crucial component in fostering the professional competence of pre-service teachers. However, existing studies have primarily focused on professional competence in general, while the role of continuous pedagogical practice in developing competence in organizing social exploration activities among Early Childhood Education students has not been clearly explained. This article adopts a narrative review approach to systematically synthesize and analyze domestic and international studies on competency-based teacher education and continuous pedagogical practice. The findings indicate that continuous pedagogical practice contributes to the development of competence in organizing social exploration activities through four major mechanisms: observing and acquiring professional experience, engaging in practical tasks, self-assessment and self-regulation of competence, and developing career motivation and identity. The main contribution of this article is the proposal of a theoretical analytical framework explaining the mechanisms through which continuous pedagogical practice contributes to the development of competence in organizing social exploration activities among Early Childhood Education students. This framework enriches the theoretical foundation for competency-based teacher education and provides directions for future research as well as the design of competency-based teacher education programs.